Restoring the shattered self : a Christian counselor's guide to complex trauma - Davediuk Gingrich, Heather, 1958- (Christian Association for Psychological Studies Bks., 2020)
"Many counselors are not adequately prepared to help those suffering from complex posttraumatic stress disorder (C-PTSD). In this updated text, Heather Davediuk Gingrich provides an essential resource for Christian counselors, ably integrating the established research on trauma therapy with insights from her own thirty years of experience and an understanding of the special concerns related to Christian counseling"--